A ternary sulphonium composite Cu3BiS3/S as cathode materials for lithium–sulfur batteries - Gao, X.; Wang, Y.; Ma, Z.; Jiang, W.; Zou, Y.; Lu, Chunsheng (Springer, 2016)
In this paper, we synthesized a new cathode material (Cu3BiS3) by a solvothermal method for high-performance lithium–sulfur batteries. Cu3BiS3 with a unique flower structure was characterized using the X-ray diffraction, energy-dispersive X-ray spectrometer, and scanning electron microscopy. It is shown that the Cu3BiS3/S flower exhibits a high initial capacity of 1343 mAh g-1 at 0.2 C, and although a capacity fade in subsequent cycles occurs due to polysulfide dissolution and shuttle mechanism, 487 mAh g-1 at 0.2 C can be retained after 100 cycles with the 90–95 % coulombic efficiency.